Viabilidade agroeconômica da cenoura adubada com jitirana. - Oliveira, Mychelle Karla Teixeira de (2009)
Green manure can assume an important role in the development of cultivation techniques that improve the use of crop residues. Among the species used is the scarlet starglory (Merremia aegptya L.), spontaneous plant that is presented as a potential source for green manure in semi-arid northeast of Brazil. Two experiments were carried out to evaluate the agro-economic viability of carrot fertilized with scarlet starglory before and after carrot sowing. The first experiment was conducted at the teaching garden of the Plant Sciences Department, Universidade Federal Rural do Semi-Árido (UFERSA), Mossoró-RN, from September to December 2008, while the second one was conducted at the Rafael Fernandes Experimental Farm located in rural area of Mossoró, from September to December 2009. Both experiments were conducted in a randomized complete block design with treatments arranged in a 4 x 4 + 1 factorial scheme, with 3 replications. The first factor was composed of the quantities of scarlet starglory incorporated into the soil (5.4, 8.8, 12.2 and 15.6 t ha-1 on a dry basis), and the second factor was the times of scarlet starglory incorporation into the soil. In the first experiment, the scarlet starglory was incorporated in the times: 0, 10, 20 and 30 days before sowing of carrot - DBS, and in the second experiment the incorporation was in the times: 0, 15, 30 and 45 days after sowing of carrot - DAS. The additional treatment (control) was fertilized with 80 t ha-1 of cattle manure. The cultivar of carrot planted was 'Brasilia'. The characteristics evaluated were: plant height, leaf number per plant, dry mass of shoot, commercial productivity, scrap productivity, classified productivity, gross income and net income, rate of return, profitability index and profit per unit. There was no significant interaction between the quantities of scarlet starglory incorporated into the soil and its times of incorporation before and after carrot sowing on any of those evaluated characteristics. The highest productive performance of carrot was obtained in the amount of 15.6 t ha-1 of scarlet starglory incorporated into the soil at the time of 20 days prior to the carrot planting time and at 15 days after carrot sowing. The carrot cultivation is agro-economically viable with the use of scarlet starglory as green manure.